The fungal collaboration gradient drives root trait distribution and ecosystem processes in a tropical montane forest - M. Dantas de Paula; T. Reichert; L. F. Lugli; E. McGale; K. Pierick; K. Pierick; J. P. Darela-Filho; L. Langan; J. Homeier; J. Homeier; A. Rammig; T. Hickler; et al. (Biogeosciences)
Plant roots have a large diversity of form and function, which is also related to their degree of mycorrhizal association. This is known as the fungal collaboration gradient, where thinner roots acquire resources by themselves, and thicker roots depend on mycorrhizae. In this study, we, for the first time, implement the fungal collaboration gradient in a trait-based dynamic vegetation model (DVM, LPJ-GUESS-NTD). We test if the DVM can predict fine-root-trait distributions and estimate the effects of arbuscular-mycorrhiza-fungus (AMF)-mediated nutrient uptake on ecosystem processes along an elevation gradient in a tropical montane forest in southern Ecuador. The model reproduces the observed fine-root traits of specific root length (SRL) and AMF colonization along the elevation gradient, which ranges from low AMF colonization at 1000 m (25 %) to high AMF colonization at 3000 m (61 %). When AMF-mediated nutrient uptake is deactivated, site average biomass values are reduced by up to 80 %. Accounting for AMF-related belowground traits also affects simulated community leaf traits, suggesting linkages between below- and aboveground traits as AMF promotes more leaf-acquisitive traits. In addition, deactivation of AMF uptake reduced simulated soil C stocks by up to 68 %. The model suggests that the collaboration gradient has a substantial influence on vegetation diversity and functioning as well as soil carbon in the study system. We thus advocate more explicit treatment of fine-root traits and mycorrhizae in DVMs. The model scheme here is based on general trade-offs and could be implemented in other DVMs and be tested for other study regions.